PENGEMBANGAN MEDIA PERMAINAN ENGKLEK UNTUK MENCEGAH KECENDERUNGAN PERILAKU AGRESIF PADA ANAK - Indrayanti, Elfriza Putri; Nurmala, Meilla Dwi; Wahyuningsih, Lenny (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The purpose of this studi is to develop a preventive media in the form of the Engklek game to prevent aggressive behavior tendencies. The method used in this research is Reseach and Development (R&D) with the 4D development model by Thiagarajan, which includes the stages of Define, Design, Development, and Disseminate. The trial subjects were collected through questionnaires and literature review. The develop product was validated by experts. The results of the expert validation showed a score of 75% from media and material experst (Feasible), 89.28% from language experts (High Feasible), and 93.75% from practitioners (High Feasible), resulting in an average score of 86.1, categorized as “High Feasible”. Therefore, it can be concluded that the Engklek game media is highly feasible for implementation.